The Trends of Psychological Status of People Entering from High-Risk Areas of COVID-19 Coronavirus During the Quarantine in Dedicated Hotels: A Longitudinal Survey Study from Guangzhou, China - Deng Y; Shi L; Li J; Jiang Z; Xie C; Luo S; Ling L; Lin H; Chen Z; Zhao Y; Kang L; Yuan J; et al. (Dove Medical Press, 2021)
Yanhong Deng,1,* Lishuo Shi,2,* Jianxia Li,1,* Zhipeng Jiang,3,* Chaojun Xie,4 Shuangling Luo,3 Li Ling,5 Hualiang Lin,6 Zongqiu Chen,4 Yunlong Zhao,7 Liang Kang,3 Jun Yuan,4 Weiping Wen8 1Department of Medical Oncology, The Sixth Affiliated Hospital, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, Guangzhou, 510655, People's Republic of China; 2Clinical Research Center, The Sixth Affiliated Hospital, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, Guangzhou, 510655, People's Republic of China; 3Department of Colorectal Surgery, The Sixth Affiliated Hospital, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, Guangzhou, 510655, People's Republic of China; 4Guangzhou Center for Disease Control and Prevention, Guangzhou, Guangdong Province, 510440, People's Republic of China; 5Department of Medical Statistics, School of Public Health, Sun Yat-sen University, Guangzhou, 510080, People's Republic of China; 6Department of Epidemiology, School of Public Health, Sun Yat-sen University, Guangzhou, 510080, People's Republic of China; 7Medical Department, the Sixth Affiliated Hospital, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, Guangzhou, 510655, People's Republic of China; 8Department of Otolaryngology, the Sixth Affiliated Hospital, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, Guangzhou, 510655, People's Republic of China*These authors contributed equally to this workCorrespondence: Weiping WenDepartment of Otolaryngology, The Sixth Affiliated Hospital of Sun Yat-sen University, Guangdong Provincial Key Laboratory of Colorectal and Pelvic Floor Disease, No. 26 Yuan Cun Er Heng Road, Guangzhou, 510655, People's Republic of ChinaTel +86-20-87333733Email wenwp@mail.sysu.edu.cnJun YuanGuangzhou Center for Disease Control and Prevention, No. 1, Qide Road of Baiyun District, Guangzhou, Guangdong Province, 510440, People's Republic of ChinaTel +86-20-36052333-1816Email yuanjuncom@163.comBackground: The quarantine in dedicated hotels has become an inevitable safety measure due to the frequent cross-border travel since the outbreak of COVID-19. The aim of the present study was to explore the trends in the psychological status of individuals entering from high-risk areas of COVID-19 coronavirus while quarantining in dedicated hotels.Methods: A total of 591 individuals who isolated in dedicated hotels were recruited between March and June 2020. Participants self-reported mental symptoms [Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS)] every three days during the quarantine. A mixed-effects linear regression model was used to assess the trends.Results: Participants reporting anxiety and depression symptoms at least one time during quarantine accounted for 4.5% and 18.4%, respectively. Their psychological status was alleviated during some first 9 days, and then it slightly deteriorated, which was suggested by SAS and SDS scores that were negatively correlated with the days of quarantine (T) (adjusted coefficient [β] − 0.81, 95% CI − 1.00 to − 0.62; and β − 0.75, 95% CI − 0.97 to − 0.53, respectively), and were positively correlated with the square of T (β 0.04, 95% CI 0.02 to 0.06; and β 0.04, 95% CI 0.02 to 0.06, respectively). The unemployed and 18∼ 30-year-old participants were prone to greater levels of psychological distress. No significant difference in the trend of mental health was found among different subgroups.Conclusion: The mental health of the people entering Guangzhou from high-risk areas of COVID-19 coronavirus resulted positive during the early period of quarantine in dedicated hotels, after which it deteriorated. The psychological status of individuals should be closely monitored at the beginning and after more than 9 days of quarantine, especially for individuals who are unemployed and 18∼ 30-year-old ones.Keywords: quarantine, dedicated hotels, psychological distress, COVID-19